PEMANFAATAN MEDIA PLANG UNTUK MENINGKATKAN KESADARAN PILAH SAMPAH DI DESA WERDI, KECAMATAN WONOKERTO, KABUPATEN PEKALONGAN - Safrina, Dessy Putri; Samaniyati, Intan; Adwiyah, Nailatul; Nurfairoh, Nurfairoh; Ramadhani, Rini; Hilaliyyan, Nauval; Kurniawan, Pratomo Cahyo (Sekolah Tinggi Ilmu Ekonomi AMA, 2025)
This community service activity addresses the critical issue of waste management in Werdi Village, where improper waste disposal has led to environmental and health concerns. The project implemented waste sorting signboards as an educational tool to promote better waste management practices among residents. The methodology involved a community survey to assess baseline knowledge, strategic placement of signboards at public locations, and post-implementation surveys to measure changes in awareness and behavior. Results from the post-implementation survey indicated a significant increase in community awareness regarding waste sorting and disposal. The signboards effectively communicated the importance of waste reduction, reuse, and recycling. Furthermore, observable improvements in waste management practices were noted, with more residents actively participating in waste sorting activities. The implementation of waste sorting signboards has proven to be a cost-effective and sustainable approach to enhance community awareness and promote responsible waste management. This initiative can serve as a model for other rural communities facing similar challenges, highlighting the importance of targeted educational interventions in fostering environmental stewardship